2003
DOI: 10.1523/jneurosci.23-02-00503.2003
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of Thioredoxin in Nerve Growth Factor-Mediated Signal Transduction and Neurite Outgrowth in PC12 Cells

Abstract: Thioredoxin (TRX) has a role in a variety of biological processes, including cytoprotection and the activation of transcription factors. Nerve growth factor (NGF) is a major survival factor of sympathetic neurons and promotes neurite outgrowth in rat pheochromocytoma PC12 cells. In this study, we showed that NGF induces TRX expression at protein and mRNA levels. NGF activated the TRX gene through a regulatory region positioned from -263 to -217 bp, containing the cAMP-responsive element (CRE). Insertion of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 51 publications
2
74
0
Order By: Relevance
“…The Trx promoter region contains several conserved sequences for transcription factors such as the oxidative stress responsive element (ORE) (Taniguchi et al, 1996), antioxidant responsive element (ARE) (Kim et al, 2001), and the cAMP responsive element (Bai et al, 2003). ORE is thought to be not directly involved in GGA-mediated Trx induction, because N-acetylcysteine, a potent antioxidant, had no effect on GGA- mediated Trx induction (Hirota et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Trx promoter region contains several conserved sequences for transcription factors such as the oxidative stress responsive element (ORE) (Taniguchi et al, 1996), antioxidant responsive element (ARE) (Kim et al, 2001), and the cAMP responsive element (Bai et al, 2003). ORE is thought to be not directly involved in GGA-mediated Trx induction, because N-acetylcysteine, a potent antioxidant, had no effect on GGA- mediated Trx induction (Hirota et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These neurotrophic factors confer cytoprotection against light-induced photoreceptor cell damage (LaVail et al, 1992;Cao et al, 2001). Trx is essential for the NGF-mediated neurite outgrowth in neuronal PC12 cells (Bai et al, 2003). Trx induced in the RPE contributes to cytoprotection against ischemia-reperfusion injury of the inner retina in rats (Yamamoto et al, 1997b).…”
Section: Discussionmentioning
confidence: 99%
“…It has two cysteines located in its catalytic center, and it functions as a redox regulator in cells [31,32]. Earlier studies have reported that human Trx1 is readily S-nitrosylated both in vitro and in vivo, and the NO group in S-nitrosylated Trx1 can be transferred to other proteins, such as caspase-3 (at Cys163) [33] via a process called trans-nitrosylation.…”
Section: Identification Of An S-nitrosylation Site In Thioredoxinmentioning
confidence: 99%
“…In general, the stimuli that promote Trx expression are also capable of promoting its intracellular movement (Bai et al, 2003;Watson et al, 2003). We herein investigated if activation of PPAR␣ could induce Trx translocation from cytosol to nucleus.…”
Section: Ppar␣ Induces the Translocation Of Trx To Nucleusmentioning
confidence: 99%
“…Trx is a cytosolic protein and shuttles between cytoplasm and nucleus under many circumstances (Bai et al, 2003;Watson et al, 2003). To study the potential intranuclear effect of Trx on regulation of PPAR␣ transcriptional activity, a possible way is to deliberately in- crease nucleus-localized Trx.…”
Section: Down-regulation Of Ppar␣ Transcriptional Activity By Ectopicmentioning
confidence: 99%